Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/term.2053
|View full text |Cite
|
Sign up to set email alerts
|

Viability and neuronal differentiation of neural stem cells encapsulated in silk fibroin hydrogel functionalized with an IKVAV peptide

Abstract: Three-dimensional (3D) porous scaffolds combined with therapeutic stem cells play vital roles in tissue engineering. The adult brain has very limited regeneration ability after injuries such as trauma and stroke. In this study, injectable 3D silk fibroin-based hydrogel scaffolds with encapsulated neural stem cells were developed, aiming at supporting brain regeneration. To improve the function of the hydrogel towards neural stem cells, silk fibroin was modified by an IKVAV peptide through covalent binding. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 47 publications
3
84
0
Order By: Relevance
“…Silk is produced by silkworm (Bombyx mori) that comprises 75% fibroin and 25% sericin and carbohydrates . Silk is biocompatible, biodegradable and has good mechanical properties that because of these features is used in various industries, and also commonly used in the medicine as surgical sutures. Because of high biocompatibility of silk, it can be used as a scaffold for increasing the growth of many stem cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silk is produced by silkworm (Bombyx mori) that comprises 75% fibroin and 25% sericin and carbohydrates . Silk is biocompatible, biodegradable and has good mechanical properties that because of these features is used in various industries, and also commonly used in the medicine as surgical sutures. Because of high biocompatibility of silk, it can be used as a scaffold for increasing the growth of many stem cells .…”
Section: Discussionmentioning
confidence: 99%
“…Silk is biocompatible, biodegradable and has good mechanical properties that because of these features is used in various industries, and also commonly used in the medicine as surgical sutures. Because of high biocompatibility of silk, it can be used as a scaffold for increasing the growth of many stem cells . Moreover, degradation of silk is 6 months in the body and within 2 years is completely decomposed, so it can be used as a good scaffold in tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The storage modulus of the IKVAV‐modified silk fibroin hydrogel was increased from 1.3 to 2.9 kPa. Neuronal stem cells encapsulated in the modified hydrogel showed higher β3 tubulin and MAP 2 expression …”
Section: Cell Culture and Differentiationmentioning
confidence: 99%
“…The effect of IKVAV in neuronal differentiation and tissue engineering was assessed by comparing natural silk fibroin hydrogel covalently modified with IKVAV with unmodified hydrogel. The study showed that the hydrogel modified with IKVAV can increase cell viability and neuronal differentiation when compared with cells encapsulated with silk fibroin hydrogel alone (Sun et al, ). Recently, studies with synthetic PuraMatrix™ covalently combined with the IKVAV motif showed promising results by differentiating NSCs toward neurons and astrocytes without the addition of growth factors (Sun et al, ).…”
Section: Biomaterialsmentioning
confidence: 99%